Hydrothermal Synthesis, Structure and Optical Properties of Organic-Inorganic Hybrid Material Containing Divanadium Hexatungstate as Subunit - WANG, CHONG-CHEN (Asian Journal of Chemistry, 2010)
A hydrothermal reaction of NH4VO3, WO3, CoCl2 and 4,4'-bipyridine yields a novel organic-inorganic hybrid compound, Co(V2W4O19) (bpy)(Hbpy)2 (bpy= 4,4'-bipyridine) (C30H26N6CoO19V2W4, Mr = 1670.78), which was characterized by elemental analysis, IR, singlecrystal X-ray diffraction analysis and UV-Vis-NIR diffuse reflectance spectrum. It crystallizes in monoclinic, space group C2/c with a = 20.187(2) Å, b = 11.6596(13) Å, c = 16.3043(17) Å, β = 96.472(2)º, V = 3813.2(7) Å3, Z = 4, Dc = 2.910 Mg/m3, μ = 12.998 mm-1 and F(000) = 3076. The final R = 0.0556 and wR = 0.1523 for 3343 observed reflections with I > 2σ(I). In the crystal, each Co(II) is six-coordinated by two oxygen atoms from two [V2W4O19]4- and two nitrogen atoms from two bidentate bpy ligands and two nitrogen atoms from two protonated and terminal bpy ligands. The Co(V2W4O19) (bpy)(Hbpy)2 (bpy= 4,4'-bipyridine) is found to have an optical energy gap of 2.3 eV from UV-Vis-NIR diffuse reflectance spectrum.